Implementation of Social Media as a Digital Marketing Strategy using Aida Analysis in Event Organizers - Rahma, Alvionita Zakiyatur; Kustini, Kustini (Formosa Journal of Applied Sciences, 2024)
Event Organizer is a team that conceptualizes an event and implements and evaluates each agenda that has been implemented. To make the wishes and dreams of many people come true, especially at weddings, event organizers offer professional services that can reach the entire community to make these dreams come true. Having a professional team such as an Event Organizer greatly influences the success of an event, from small events organized by companies, concerts or public entertainment to personal events such as weddings. The people of Surabaya already know and trust the professional service team that can plan wedding processions, namely Mahar Agung Organizer. In introducing the Creative Industry Business, Mahar Agung Organizer uses digital promotion strategies through social media such as YouTube, Instagram, TikTok, and Websites to carry out promotions. This research aims to describe strategies for how an event organizer business can develop social media such as Instagram and TikTok as the main promotional media to get clients. Through AIDA analysis (attention, interest, desire, action). The method in this research is descriptive qualitative by describing in detail and analyzing the results of field observations, literature studies, interviews and documentation. This research shows the results that social media has a big influence on clients' interest in using the professional services of Mahar Agung Organizer which always has attractive offers and informative content regularly.